The role of government innovation in achieving competitive advantage in the Education Department in Bisha Governorate; From the point of view of the staff - Alghamdi, Mariam Khader; Gheith, Nirvana Abdulrahman (Journal of Economic, Administrative and Legal Sciences, 2022)
The aim of this study is to identify the role of governmental innovation by the following dimensions (administrative innovation, service innovation, technological innovation, openness to ideas, risks) in achieving competitive advantage from the point of view of administrative staff in the Education Department in Bisha Governorate. The study in its analysis relied on the descriptive analytical approach. A questionnaire was applied as data collection tool. The study population consisted of (1014) employees. The sample of the study was (323) employees in the Department of Education in Bisha. The data were statistically processed using the Statistical Package for Social Sciences (SPSS), from the point of view of employees in the Department of Education in Bisha. The results showed a high application of both governmental innovation with mean scores of (3.99) and competitive advantage with mean scores of (4.06) respectively. Technological innovation ranked among the dimensions of governmental innovation with an average of (4.08), followed by service innovation. As for the dimensions of administrative innovation and openness to ideas, it occupies the third place. The risks dimension takes the fourth place with an average of (4.08). The results proved the existence of a statistically significant effect at (0.01) of governmental innovation in achieving competitive advantage. The study recommended the necessity of encouraging innovation and enhancing its opportunities by supporting change and showing a greater willingness to bear the risks resulting from the application of new ideas, and to allow greater freedom to participate in finding solutions and generating new ideas, by increasing flexibility and reducing routine work procedures and policies, and through supporting and motivating.